Redistribution and Effect of Various Elements on the Morphology of Primary Graphite in Cast Iron. (27th June 2013) - Lacaze, J.; Valle, N.; Theuwissen, K.; Sertucha, J.; El Adib, B.; Laffont, L.
Abstract : It has been shown repeatedly that many elements present as traces or at low level can affect graphite shape in cast irons. As part of a long term project aimed at clarifying the growth and the alteration of spheroidal graphite, a study on the effect of a few elements (Cu, Sn, Sb, and Ti) on primary graphite growth was undertaken and analysed with reference to an alloy without any such additions. This work was performed by remelting alloys in graphite crucibles thus saturating the melt in carbon and enabling primary graphite to grow by controlled cooling of the melt above the eutectic temperature. Primary graphite growth in the reference alloy was observed to be lamellar, while the added elements were found to affect bulk graphite and to modify its outer shape, with Sb leading eventually to rounded agglomerates together with wavy lamellae. Secondary ion mass spectrometry was used to analyze the distribution of elements, and no build-up of trace elements at the graphite surface could be observed. Instead, it is established that the perturbation of bulk graphite is associated with inhomogeneous distribution of metallic elements inside graphite precipitates.